Sleep‐spindle frequency: Overnight dynamics, afternoon nap effects, and possible circadian modulation - Bódizs, Róbert; Horváth, Csenge G.; Szalárdy, Orsolya; Ujma, Péter P.; Simor, Péter; Gombos, Ferenc; Kovács, Ilona; Genzel, Lisa; Dresler, Martin (Journal of sleep research, 2022)
Summary Homeostatic and circadian processes play a pivotal role in determining sleep structure, timing, and quality. In sharp contrast with the wide accessibility of the electroencephalogram (EEG) index of sleep homeostasis, an electrophysiological measure of the circadian modulation of sleep is still unavailable. Evidence suggests that sleep‐spindle frequencies decelerate during biological night. In order to test the feasibility of measuring this marker in common polysomnographic protocols, the Budapest‐Munich database of sleep records (N = 251 healthy subjects, 122 females, age range: 4–69 years), as well as an afternoon nap sleep record database (N = 112 healthy subjects, 30 females, age range: 18–30 years) were analysed by the individual adjustment method of sleep‐spindle analysis. Slow and fast sleep‐spindle frequencies were characterised by U‐shaped overnight dynamics, with highest values in the first and the fourth‐to‐fifth sleep cycle and the lowest values in the middle of the sleeping period (cycles two to three). Age‐related attenuation of sleep‐spindle deceleration was evident. Estimated phases of the nadirs in sleep‐spindle frequencies were advanced in children as compared to other age groups. Additionally, nap sleep spindles were faster than night sleep spindles (0.57 and 0.39 Hz difference for slow and fast types, respectively). The fine frequency resolution analysis of sleep spindles is a feasible method of measuring the assumed circadian modulation of sleep. Moreover, age‐related attenuation of circadian sleep modulation might be measurable by assessing the overnight dynamics in sleep‐spindle frequency. Phase of the minimal sleep‐spindle frequency is a putative biomarker of chronotype.